x+3x-4=6

Simple and best practice solution for x+3x-4=6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for x+3x-4=6 equation:


Simplifying
x + 3x + -4 = 6

Reorder the terms:
-4 + x + 3x = 6

Combine like terms: x + 3x = 4x
-4 + 4x = 6

Solving
-4 + 4x = 6

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '4' to each side of the equation.
-4 + 4 + 4x = 6 + 4

Combine like terms: -4 + 4 = 0
0 + 4x = 6 + 4
4x = 6 + 4

Combine like terms: 6 + 4 = 10
4x = 10

Divide each side by '4'.
x = 2.5

Simplifying
x = 2.5

See similar equations:

| 2lne^5=y | | 7x+54+42=180 | | 0.60x=12 | | 9s=-1+10s | | -6+5w=6w | | -26=-6+4v | | -8t-2=-9t | | 3x^2-32x=-65 | | x+.25x=75 | | 2x-1=1.7 | | 2x^2+20x+70=0 | | Ptanx+qtanx=tanz | | 9x-4+122=180 | | (8+3)4=8*4+3*4 | | 45j+-36j-3j-45=-87 | | (4x-22)+(10x-4)+(x+11)=180 | | -8a+14b+61=0 | | 2z-z+2z-z-2=18 | | 3x+7y=-10 | | (9x+3)+(5x-2)+(11x-21)=180 | | 6x+3+75=90 | | 2a-a-a+3a-3=18 | | 1/8(4,200) | | 28x+14y=2 | | 3s-3s+s+1=13 | | 6x(2x+7)=48 | | 10j-j-2j=7 | | 4X+5=-2(X+3) | | 3x^2+18x-120= | | 25=9x+4-2x | | 3(p+2)=3(2p+4)+9 | | -3/4x=-9 |

Equations solver categories